Pengaruh Hedging, Kompensasi Eksekutif dan Gender Diversity Terhadap Agresivitas Pajak - Kurnia, Kurnia; Yahfis, Wulandari (Akuisisi : Jurnal Akuntansi, 2025)
Studying the impact of hedging, executive compensation, and board gender diversity on tax aggressiveness is the main objective of this study. The mining sector that has been listed on the Indonesia Stock Exchange during the 2017-2021 period is used as the population in this study. The purposive sampling technique was used in selecting the sample, where as many as 85 observations were obtained from 17 mining companies that met the sample criteria. This study uses a quantitative approach and panel data regression as an analytical technique with the help of Eviews 12 software. The results of this study prove that hedging, executive compensation, and gender diversity have a simultaneous effect on aggressive tax avoidance. Based on the results of the partial test, it was found that hedging did not affect aggressive tax avoidance, executive compensation had a negative impact on aggressive tax avoidance, and gender diversity had a positive effect on mining company tax aggressiveness in 2017–2021